Facile preparation of magnetic carbon nanotubes-immobilized lipase for highly efficient synthesis of 1, 3-dioleoyl-2-palmitoylglycerol-rich human milk fat substitutes. (1st August 2017) - Zheng, Mingming; Wang, Shi; Xiang, Xia; Shi, Jie; Huang, Juan; Deng, Qianchun; Huang, Fenghong; Xiao, Junyong
Highlights: A novel magnetically retrievable immobilized lipase was prepared. OPO-rich TAGs was efficiently synthesized by enzymatic acidolysis. The activity and reusability of CLL @mMWCNTs was superior to Lipozyme RM IM. Production of OPO-rich TAGs was performed using lard and restructured palm oil. Abstract: In this study, Candida lipolytica lipase ( CLL ) was immobilized on magnetic multi-walled carbon nanotubes (mMWCNTs) via hydrophobic and cation-exchange interaction. The resultant immobilized CLL showed much better thermal stability, biocatalyst activity and easier recycling than the free form. A method for efficient enzymatic acidolysis of tripalmitin (PPP) with oleic acid (OA), to produce OPO-rich TAGs, was developed, using the immobilized CLL as the biocatalyst. Under optimized conditions (2% water, 20 mg/ml enzyme, 1:6 PPP/OA, 50 °C, 2 h), the content of OPO in the final product reached 46.5%. CLL @mMWCNTs had a better activity and manipulative stability than commercial lipases. More importantly, the feasibility of CLL @mMWCNTs was also validated in the practical production of OPO-rich TAGs, using lard and restructured palm oil as the raw material. These results suggest that CLL @mMWCNTs is a promising biocatalyst for the OPO-rich TAGs production and will be helpful for the infant formula industry.